To solve the equation \( y - 82 = -12 \), follow these steps:
- Add 82 to both sides of the equation to isolate \( y \): \[ y - 82 + 82 = -12 + 82 \] This simplifies to: \[ y = 70 \]
So, the solution is \( y = 70 \).
y−82=−12y-82=-12y−82=−12
y=y=y=
3 answers
To solve the equation \( y - 82 = -12 \), follow these steps:
So, the solution is \( y = 70 \).
To solve the equation \( 2(x - 1) = 9 \), follow these steps:
Distribute the 2 on the left side: \[ 2x - 2 = 9 \]
Add 2 to both sides to isolate the term with \( x \): \[ 2x - 2 + 2 = 9 + 2 \] This simplifies to: \[ 2x = 11 \]
Divide both sides by 2 to solve for \( x \): \[ x = \frac{11}{2} \]
Therefore, the solution is: \[ x = \frac{11}{2} \]